The Presbyterians of Ulster, 1680-1730 - Whan, Robert (Boydell & Brewer, 2013)
The Presbyterian community in Ulster was created by waves of immigration, massively reinforced in the 1690s as Scots fled successive poor harvests and famine, and by 1700 Presbyterians formed the largest Protestant community in the north of Ireland. This book is a comprehensive survey and analysis of the Presbyterian community in this important formative period. It shows how the Presbyterians formed a highly organised, self-confident community which exercised a rigorous discipline over its members and had a well-developed intellectual life. It considers the various social groups within the community, demonstrating how the always small aristocratic and gentry component dwindled and was virtually extinct by the 1730s, the Presbyterians deriving their strength from the middling sorts - clergy, doctors, lawyers, merchants, traders and, in particular, successful farmers and those active in the rapidly growing linen trades - and among the laborious poor. It discusses how Presbyterians were part of the economically dynamic element of Irish society; how they took the lead in the emigration movement to the American colonies; and how they maintained links with Scotland and related to other communities, in Ireland and elsewhere. Later in the eighteenth century the Presbyterian community went on to form the backbone of the Republican, separatist movement. ROBERT WHAN obtained his Ph.D. in History from Queen's University, Belfast